Sedation and its Potential Risks in Children with Autism Spectrum Due to Drug Overlaps: A Critical Review - Herculano Ramirez Floro Alonso; Mônica Vilela Heimer; Rafael Vrijdags Calado; João Victor Farias da Silva; Renata Matos Lamenha Lins; Dayse Andrade Romão; Daniela Maria Carvalho Pugliesi; Valdeci Elias dos Santos Junior (Association of Support to Oral Health Research (APESB), 2024)
Objective: To analyse pharmacological overlap in patients with autism spectrum disorder (ASD) under conscious sedation in a dental office environment, identifying any potential risks and complications. Material and Methods: A critical review was conducted by selecting articles from online databases (Pubmed and Lilacs), using a search algorithm and eligibility criteria. The Medscape® platform was used to verify interactions between drugs commonly used by patients with ASD and medications used for sedation in paediatric dentistry. Results: Due to their polydrug use, children with ASD are at risk of complications, namely Serotonin Syndrome (SS), Neuroleptic Malignant Syndrome (NMS), increase or decrease of the QT interval (QTi) and Torsade de Pointes (TdP), due to pre-existence of metabolic syndrome, deepening the sedation level or even leading to a decrease in the sedative capacity of the drugs used. Conclusion: It is essential to assess better drug interaction in ASD patients submitted to sedation. The severity of the disorder and the need for sedation for dental treatment are directly proportional. However, increases in sedative doses tend to increase risks and complications in children with ASD.